Establishment of a Rapid Micropropagation System for Kaempferia parviflora Wall. Ex Baker: Phytochemical Analysis of Leaf Extracts and Evaluation of Biological Activities - Han Yong Park (Plants, 2021)
This study aimed to establish a rapid in vitro plant regeneration method from rhizome buds of Kaempferia parviflora to obtain the valuable secondary metabolites with antioxidant and enzyme inhibition properties. The disinfection effect of silver oxide nanoparticles (AgO NPs) on rhizome and effects of plant growth regulators on shoot multiplication and subsequent rooting were investigated. Surface sterilization of rhizome buds with sodium hypochlorite was insufficient to control contamination. However, immersing rhizome buds in 100 mg L−1 AgO NPs for 60 min eliminated contamination without affecting the survival of explants. The number of shoots (12.2) produced per rhizome bud was higher in Murashige and Skoog (MS) medium containing 8 µM of 6-Benzyladenine (6-BA) and 0.5 µM of Thidiazuron (TDZ) than other treatments. The highest number of roots (24), with a mean root length of 7.8 cm and the maximum shoot length (9.8 cm), were obtained on medium MS with 2 µM of Indole-3-butyric acid (IBA). A survival rate of 98% was attained when plantlets of K. parviflora were acclimatized in a growth room. Liquid chromatography with tandem mass spectrometry (LC-MS/MS) was used to determine the chemical profile of K. parviflora leaf extracts. Results showed that several biologically active flavonoids reported in rhizomes were also present in leaf tissues of both in vitro cultured and ex vitro (greenhouse-grown) plantlets of K. parviflora. We found 40 and 36 compounds in in vitro cultured and ex vitro grown leaf samples, respectively. Greenhouse leaves exhibited more potent antioxidant activities than leaves from in vitro cultures. A higher acetylcholinesterase inhibitory ability was obtained for greenhouse leaves (1.07 mg/mL). However, leaves from in vitro cultures exhibited stronger butyrylcholinesterase inhibitory abilities. These results suggest that leaves of K. parviflora, as major byproducts of black ginger cultivation, could be used as valuable alternative sources for extracting bioactive compounds.